The impact of gender-affirming interventions on eating disorder diagnosis risk among transgender and gender-diverse individuals - Matthew Loria; Tomasz Tabernacki; Elad Fraiman; Jaime Perez; Jessica Abou Zeki; Julia Palozzi; Carly Goldblatt; Shubham Gupta; Kirtishri Mishra; Megan McNamara; Swagata Banik (Communications Medicine)
Abstract Background The objective of this study is to evaluate the risk of being diagnosed with an eating disorder among transgender and gender-diverse (TGD) individuals, specifically examining how this risk differs following gender-affirming medical therapy (GAMT). Methods The study utilizes electronic medical record (EMR) data from the TriNetX database. A total of 90,955 TGD individuals were identified in the TriNetX database. TGD individuals were divided into cohorts according to gender-affirming interventions they received. To assess the risk of eating disorder diagnoses across groups, we applied a Cox proportional hazards model with gender-affirming care as a time-varying covariate. Results Here we show that transfeminine individuals receiving hormone therapy (HT) have a significantly higher likelihood of being diagnosed with an eating disorder compared to those without intervention (HR:1.67, 95% CI:1.41, 1.98). Conversely, transmasculine individuals on HT exhibit a reduced risk of being diagnosed with an eating disorder relative to those without intervention (HR: 0.83, 95% CI: 0.76, 0.90). Conclusions After undergoing gender-affirming medical therapy, the risk of eating disorder diagnosis increases for transfeminine individuals and decreases for transmasculine individuals. The observed differences in risk between transfeminine and transmasculine individuals on GAMT may be attributed to factors such as gendered societal norms, variations in screening practices, and the physiological effects of hormone therapy on eating disorder symptomatology. Further research is needed to clarify these influences and support tailored interventions.